The SISAP: A New Screening Instrument for Identifying Potential Opioid Abusers in the Management of Chronic Nonmalignant Pain Within General Medical Practice - Robert B Coambs; Josée L Jarry; Anusha C Santhiapillai; Rixi V Abrahamsohn; Cristina M Atance (Pain Research and Management)
BACKGROUND: Many physicians are overly cautious about prescribing opioids for chronic pain because of fears of iatrogenic addiction. However, in patients with chronic pain, addiction to opioid analgesics is exceedingly rare when there is no prior history of alcohol or drug abuse.